Measurement of methane and nitrous oxide fluxes in Bodrogköz, Hungary; preliminary results - Horváth, László (Acta Biologica Szegediensis, 2008)
Soil fluxes of methane and nitrous oxide were determined for five different plant communities in Bodrogköz, Hungary. As the direction of methane flux (emission or uptake) depends on the soil characteristics (mostly on soil moisture) bi-directional fluxes were observed in 2006 and 2007, the sink and source processes were practically balanced. Average soil nitrous oxide emission fluxes for the period of 2006-2007 was 1.2 μg N m-2 h-1 for tall vegetation while for low vegetation it was 2.4 μg N m-2 h-1. Taking into account the total atmospheric N-input, 0.7 to 1.6 per cent of deposited nitrogen is emitted from the soils in the form of N2O as an intermediate product of soil denitrification processes.